Macleod's clinical OSCEs - O'Neill, Paul (Paul A.) (Churchill Livingstone/Elsevier, 2016)
Based on Macleod's clinical examination / edited by Graham Douglas, Fiona Nicol, Colin Robertson. Thirteenth edition. 2013